(untitled) (Medico Legal Update, 2021)
Background: Aging is the process of progressive change in the biological, psychological and social structure of individuals’. Quality is affected by both the technical performance of providers and the extent to which a system reaches those in need. Aim of Study: The study aimed to assess the quality of health care delivered to old age and factors affecting quality of health care. Subjects and Method: The study was conducted in the inpatient units at Beni-Suef university hospital. Study sample were nurses and patients: For nurses; all nurses who have experience more than one year at medical surgical department, urinary tract diseases, and provide care for geriatric patients was included in this study. For patients; convenient sample from the pre mentioned setting. Two data collection tools were used to carry out the current study namely; structured Interviewing questionnaire and observational checklists. Results: 26% of the nurses were satisfied according to work place satisfaction, the same was percent unsatisfied according to work place satisfaction, and the rest of them (48%) had average level of satisfaction. 58% of nurses had unsatisfied level according to their performance. (42%) of participants had satisfied level according to their performance. Conclusion and Recommendations: 38% of patients had fair level about their evaluation, 33% of them had excellent level about their evaluation to quality of health care, and 29% of them had average level and 41% of them had negative level of satisfaction. Periodic assessment of nurses› perception about quality of care of elderly patient. Regular implementation of training programs regarding quality of care.